Conhecimento ecológico local, técnicas de pesca e uso dos recursos pesqueiros em comunidades da área de proteção ambiental Barra do Rio Mamanguape, Paraíba, Brasil - Cortez, Creuza Soares (2010)
This study was conducted among three coastal communities: Aritingui, Taberaba and Tavares, located on the right of the estuary of Mamanguape River (EMR) in Paraíba, and incorporated in the Environmental Protection Area of the namesake river. Its main objective is to study the local ecological knowledge and use of wildlife resources by fishermen and collectors of these communities. This work had its theoretical and methodological focus in Ethnoecology. The sampling was intentionally non-random, where the respondents were previously defined according to the dedication and frequency in fishing activities. The fieldwork took place between the months of October 2008 and November 2009. Free unstructured interviews and direct observations were conducted with the purpose of studying aspects of the interaction between the target communities and the mangrove-estuary complex. From the free unstructured interviews, structured interviews were conducted to collect data on the exploration, utilization and conservation of resources from the mangrove-estuary of Mamanguape River. The data were analyzed using the model of unity of the various individual skills seeking to juxtapose ethnoecological to scientific knowledge. In developing the mental maps, one key informant was chosen in each community and each was asked to design, with reference to their community, the estuary with the main collection of fishery resources. The oral map was obtained from tours guided by key informants along the EMR and was to appoint the main sampling sites. Fishermen cited 13 folk generic species: 6 species of fish, 5 crustacean species and 2 species of mollusks. The species of fish most often cited was Bathygobius soporator, of crustacean was Cardisoma guanhumi and of mollusk was Crassostrea sp., which are used for consumption, with marketing only of the surplus. Fishermen perceive the spatial distribution of wildlife resources and categorize them in etnohabitats ( mangrove fish , Camboa fish ), microhabitats ( fish of strain , fish of hole and fish of lodge ) and vertical distribution ( ground fish and water flower fish ). They also showed a wide knowledge of the trophic and reproductive behavior of the most explored species. From the mental and oral maps, accurate spatial perception related to fishing sites and grooming was registered. The fishermen in the Aritingui, Taberaba and Tavares communities show detailed ethnobiological knowledge, consistent with Western science. The knowledge that these fishermen hold on the distribution of resources and its ecology, and environmental perception, is a tool valuable enough to be embedded in socio-economic plans as well as in management, conservation and sustainable use of wildlife studies.